Performance-related pay and labor productivity - Claudio Lucifora (IZA World of Labor, 2015)
Many firms offer employees a remuneration package that links pay to performance as a means of motivation. It also improves efficiency and reduces turnover and absenteeism. The effects on productivity depend on the type of scheme employed (individual or group performance) and its design (commissions, piece-rate or sharing schemes). Individual incentives demonstrate the largest effect, while group or team incentives are smaller in magnitude. The case for government intervention through tax breaks and other financial incentives is highly debated due to differences across firms and the potential for economic inefficiencies.
Keywords: J31; J33; J52; L61; 330; performance-related pay; productivity; pay incentives; financial participation